2013
DOI: 10.1149/2.017308jss
|View full text |Cite
|
Sign up to set email alerts
|

Trade-Off between Parasitic Deposition and SiC Homoepitaxial Growth Rate Using Halogenated Si-Precursors

Abstract: We discuss the use of halogenated Si-X precursors, compared to the traditional silane precursor, to increase the growth rate of thick, high quality SiC homoepitaxial layers by chemical vapor deposition for power electronics applications. These precursors reduce gas phase nucleation and parasitic deposition to increase the availability of reactive Si-species at the SiC growth front due to their less reactive nature compared to silane. While less reactive Si-X species are expected to provide lower activity of Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…In most cases, Cl has been used for this purpose. Recent research also found that Br and F chemistries are applicable to SiC CVD [33][34][35] .…”
Section: Chemical Vapor Deposition (Cvd) Of Sicmentioning
confidence: 98%
“…In most cases, Cl has been used for this purpose. Recent research also found that Br and F chemistries are applicable to SiC CVD [33][34][35] .…”
Section: Chemical Vapor Deposition (Cvd) Of Sicmentioning
confidence: 98%
“…Moreover, since a thick drift layer of at least 10 μm or more is required for most of the SiC power devices, a large amount of by-product due to iteration of epitaxial growth are formed in CVD reactor, having harmful effect on epitaxial growth [13], [14]. In order to reduce the harmful effect on the epitaxial growth due to by-product in the reactor, short maintenance period is required for mass production of 4H-SiC epitaxial films, resulting obstacles to high productivity.…”
Section: Influence and Suppression Of Harmful Effects Due To By-product In Cvd Reactor For 4h-sic Epitaxymentioning
confidence: 99%
“…In the vertical CVD reactor to grow 4H-SiC films, it is known that parasitic deposition is likely to be formed at around gas inlet which is heated by radiation from the high temperature wafer and hot-wall. It has been reported that Si droplets and SiC particles are attached to the wafer due to by-product formed in the gas inlet [14]. In this paper, halogenated Si precursors instead of SiH 4 gas was proposed to reduce the byproduct formed in the gas inlet.…”
Section: B Influence Of Si Deposit Formed On the Gas Nozzlesmentioning
confidence: 99%
“…Good 4H-SiC homoepitaxial growth can be achieved by i) Increasing temperature to encourage desorption of growth species from the terrace surfaces, although this can also reduce growth rate by increasing desorption from step-sites; ii) by using off-cut substrates as discussed above and iii) by changing the chemistry of the CVD process, which in turn affects the surface kinetics, thereby breaking certain inherent tradeoffs in the growth [18]. Previous studies have used this method to varying degrees of success [19], particularly with the addition of halogens to the growth to increase the volatility of growth species on the terrace surfaces.…”
Section: Introductionmentioning
confidence: 99%